The Influence of Technology Literacy and Financial Literacy on Small Business Performance Mediated by Digital Finance Access - Indryana, Indryana; Sujono, Sujono; Hamid, Wahyuniati (International Journal of Management and Education in Human Development, 2024)
This study aims to examine the effect of technological literacy, financial literacy on small business performance. This study also examines the moderating role of digital financial access. The population in this study were all small businesses in Kendari City, totaling 1,108 small businesses. The number of samples in this study were 294 respondents, which were selected using purposive sampling method. The data collection technique used a questionnaire in the form of a well-organized list of questions through survey media. The analysis model used is structure equation modeling with the covariance base model method or known as SEM-PLS. The results found that financial literacy and technological literacy have a significant positive effect on company performance (small businesses). Digital financial access acts as a mediating influence of financial literacy and technological literacy on firm performance (small businesses).